Effect of the orientation on the photooxidation behaviour of polymer films. (October 2016) - La Mantia, F.P.; Mistretta, M.C.; Ceraulo, M.; Koci, P.
Graphical Abstract: Highlights: Effect of orientation on the photooxidation. Increase of the effect of the orientation with crystallinity. Increase of the durability with orientation. Abstract: The effect of the orientation on the photooxidation of polymers is quite controversial. Both improvement of the photo-resistance along the oriented direction and worsening of the photooxidation kinetic have been reported. In this work the effect of the orientation has been investigated on films of PE, PP and PET with different degree of orientation and crystallinity. The results show that the photo-stability, measured from the decay of the elongation at break curve as a function of the irradiation time, improves in the more oriented direction, but this is more and more relevant with increasing the crystallinity degree. It has been hypothesized that the reinforcing action of the oriented crystalline fibers could be responsible for this behaviour. More crystalline fibers are present, more reinforcing action is shown and this can explain the remarkable effect of both orientation and crystallinity.